2021
DOI: 10.1021/acsomega.1c00772
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward a Large-Scale Synthesis of Molnupiravir (MK-4482, EIDD-2801) from Cytidine

Abstract: Molnupiravir (MK-4482, EIDD-2801) is a promising orally bioavailable drug candidate for the treatment of COVID-19. Herein, we describe a supply-centered and chromatography-free synthesis of molnupiravir from cytidine, consisting of two steps: a selective enzymatic acylation followed by transamination to yield the final drug product. Both steps have been successfully performed on a decagram scale: the first step at 200 g and the second step at 80 g. Overall, molnupiravir has been obtained in a 41% overall isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…As more information becomes available, it is possible that other promising drugs such as imatinib, infliximab, or molnupiravir may be approved by the WHO if initial clinical results from preprints are confirmed in larger peer-reviewed randomized, controlled trials. A recently published study (October 2021) has found that the 5-day course of the antiviral molnupiravir taken at 800 mg BD could profitably be sold for less than US $20 per person when calculated using Panjiva API export data [ 41 ], and using raw ingredients and a synthetic process with solvent capture this could drop to below US $5 per course [ 42 ]. When we ran our own preliminary analysis using API data available in June 2021 and calculated molnupiravir\'s estimated cost of production, we found a potential cost that was more than 10× higher than the later October study.…”
Section: Discussionmentioning
confidence: 99%
“…As more information becomes available, it is possible that other promising drugs such as imatinib, infliximab, or molnupiravir may be approved by the WHO if initial clinical results from preprints are confirmed in larger peer-reviewed randomized, controlled trials. A recently published study (October 2021) has found that the 5-day course of the antiviral molnupiravir taken at 800 mg BD could profitably be sold for less than US $20 per person when calculated using Panjiva API export data [ 41 ], and using raw ingredients and a synthetic process with solvent capture this could drop to below US $5 per course [ 42 ]. When we ran our own preliminary analysis using API data available in June 2021 and calculated molnupiravir\'s estimated cost of production, we found a potential cost that was more than 10× higher than the later October study.…”
Section: Discussionmentioning
confidence: 99%
“…As more information becomes available, it is possible that other promising drugs such as imatinib, infliximab or molnupiravir may be approved by the WHO if initial clinical results from pre-prints are confirmed in larger peer reviewed RCTs. A recently published study (October 2021) has found that the 5-day course of the anti-viral molnupirivir taken at 800mg BD could profitably be sold for less than $20 per person when calculated using Panjiva API export data [41] and using raw ingredients and a synthetic process with solvent capture this could drop to below $5 per course [42]. When we ran a preliminary analysis of API Panjiva data of molnupiravir in June 2021, we found a treatment course would cost more than x10 fold higher.…”
Section: Discussionmentioning
confidence: 99%
“…Ahlqvist, Grace P et al [ 28 ] described a two-step supply-centered and chromatography-free synthesis of molnupiravir from cytidine. By undergoing transamination to yield, the final medicine product followed a selective enzymatic acylation.…”
Section: Review Of Recent Articles On Synthetic Methods Of Molnupiravirmentioning
confidence: 99%